Benefits of simulations for skill training in anesthesiology residency: a systematic review - Sotério de Oliveira, Nádia Marisa (2025)
Introduction: Medical training requires the integration of theoretical knowledge and practical skills to prepare anesthesiology residents to handle the clinical challenges of the specialty. In this context, the use of simulations has proven to be essential, allowing the development of both technical and non-technical competencies in a controlled and safe environment. Objective: Identify and synthesize evidence on the benefits of using simulations for skills training in anesthesiology residency. Method: A literature review was conducted following PRISMA guidelines, analyzing studies from 2019 to 2024 in the PubMed and LILACS databases. The review focused on types of simulations, skills developed, and clinical impact. Results: Thirteen studies, published between 2020 and 2024, were selected, which highlighted benefits such as greater accuracy in ultrasound-guided procedures, effective crisis management and improved patient safety. Technologies such as virtual reality and artificial intelligence were described as tools capable of accelerating the learning curve and enhancing educational experience. Despite these advancements, the implementation of simulation-based environments faces significant challenges. The high cost of equipment, the need for advanced infrastructure, and the lack of standardized methodologies hinder widespread adoption. In resource-limited regions, these barriers are even more pronounced. Suggested strategies include the use of cost-effective models, structured feedback, remote training programs, periodic session repetition, and the integration of simulations into medical curricula. Conclusion: Simulations are essential in anesthesiology training, enhancing technical skills and patient safety. Despite cost and logistical challenges, strategies such as accessible technologies and structured feedback can improve their effectiveness and broaden their reach.